2016
DOI: 10.2147/ccid.s104392
|View full text |Cite
|
Sign up to set email alerts
|

The effects of continuous application of sunscreen on photoaged skin in Japanese elderly people – the relationship with the usage

Abstract: Since photoaging of skin is caused by chronic sun exposure, it is well-recognized that regular sunscreen use can help prevent photoaging of skin in fair-skinned people. Therefore, application of sunscreen is recommended for the prevention of photoaging in many countries. However, the relationship between UV exposure and photoaging has rarely been investigated in clinical studies in Japan. In addition, there have been almost no long-term interventional studies in Japanese people. We have previously conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…To summarize, the works presented here, issued by the same group of research, fit well into a wide linkage of similar scientific objective, despite some different protocols or techniques. Regarding facial signs changes with UV exposures and photoprotection habits similar qualitative observations are present in literature for different phototypes and ancestries [51][52][53][54]. Skin photoprotection indeed remains a vivid topic of research, witnessed by many recent and excellent papers.…”
Section: Study Objective (N) Gender (W or M) Ages Protocol/methods Us...supporting
confidence: 57%
“…To summarize, the works presented here, issued by the same group of research, fit well into a wide linkage of similar scientific objective, despite some different protocols or techniques. Regarding facial signs changes with UV exposures and photoprotection habits similar qualitative observations are present in literature for different phototypes and ancestries [51][52][53][54]. Skin photoprotection indeed remains a vivid topic of research, witnessed by many recent and excellent papers.…”
Section: Study Objective (N) Gender (W or M) Ages Protocol/methods Us...supporting
confidence: 57%
“…A related protective factor, sunscreen use, was significantly associated with wrinkling (pOR 0.50, 95% CI 0.25, 0.98) with non-significant heterogeneity (I 2 = 0.00%, p = 0.387). however, studies that did not report odds ratios found non-significant associations for wrinkling with sunscreen use 39,68,81,82 ; another which stratified sunscreen use by reasons for use reporting findings of inconsistent significance 69 . Likewise, the association of sunscreen use with SSM score was non-significant (Fig.…”
Section: Modifiable Factors (Extrinsic Aging) Air Pollutionmentioning
confidence: 98%
“…The effect of broad‐spectrum UVA and UVB sunscreen (SPF 30, PF 8) on photoaged skin was investigated in a 18‐month, single‐arm interventional study in 14 Japanese (7 men and 7 women) aged 62–91 years with FST II–III 71 . Despite receiving instructions on how to apply the sunscreen, large inter‐individual differences were observed in the amount of sunscreen used, ranging from 6.47 g/month to 63.7 g/month 71 . Improvements in uneven skin tone, area, and number of pigment spots showed a good correlation with amount of sunscreen used 71 .…”
Section: Broad‐spectrum Photoprotection Recommendations To Prevent Ph...mentioning
confidence: 99%